Pendampingan Komputerisasi Dan Pelatihan Microsoft Office Di MI Miftahul Ulum Balongsari - Sujono Sujono; Ashlihah Ashlihah; Amin Awal Amaruddin; Saiful Anam; Mochamad Yusak Nur Machmudi; Muhammad Saiful Ayub (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
ABSTRACT Technology, which is currently increasingly rapid and sophisticated, is able to erode the morals and morals of the Muslim generation with the presence of various western cultures in their daily behavior. Wisdom in the use of technology has a considerable influence on the formation of children's brain abilities and will affect the level of intelligence of children, that is why we teach students at MI Miftakhul Ulum because the problems that occur in institutions today are the lack of facilities for learning. regarding technology and the lack of educators who have the ability or skill in that field. This problem causes children to be less able to recognize technology and also how to use technology. So it is felt that there is a need for learning or new subjects to get to know technology and how to use technology. This activity uses socialization, practice, and mentoring methods so that children can get to know what a computer is, how to operate it, and how to use existing technology or software on computers, especially Microsoft Office. This is carried out to provide knowledge and experience to 6th grade MI studentsand teachers. Miftahul Ulum regarding learning to use computers so that students have insight into computers and also gain experience in using and utilizing computers and as preparation for ANBK (Computer-Based National Assessment) or ANBK as a substitute for the Computer-Based National Examination or UNBK Keywords: Accompaniment, Computerization, Microsoft Office, Power Point. ABSTRAK Tekhnologi yang saat ini semakin pesat dan canggih mampu mengikis moral dan akhlaq generasi muslim dengan hadirnya berbagai budaya barat dikehidupan mereka dalam berperilaku sehari hari. Kebijaksanaan dalam penggunaan teknologi mempunyai pengaruh yang cukup besar bagi pembentukan kemampuan otak anak dan akan berpengaruh terhadap tingkat kecerdasan anak itulah yang mendasari mengapa kami melakukan pengajaran untuk siswa di MI Miftakhul Ulum di karenakan permasalahan yang terjadi di lembaga saat ini adalah tidak adanya fasilitas untuk melakukan pembelajaran mengenai tekhnologi dan kurangnya tenaga pendidik yang memiliki kemampuan atau skill di bidang tersebut. Permasalahan ini menyebabkan anak-anak kurang mampu untuk mengenal tekhnologi dan juga bagaimana cara untuk memanfaatkan tekhnologi. Sehingga dirasa perlu adanya pembelajaran atau mata pelajaran baru untuk mengenal teknologi dan bagaimana cara memanfaatkan tekhnologi. Kegiatan ini adalah menggunakan metode sosialisasi, praktik, dan pendampingan sampai anak anak dapat mengenal apa itu komputer sampai bagaimana cara mengoperasikanya dan bagaimana cara memanfaatkan teknologi atau software yang ada pada komputer khususnya Microsoft Office ini dilaksanakan untuk memberikan pengetahuan dan pengalaman kepada para siswa kelas 6 MI Miftahul Ulum mengenai pembelajaran menggunakan komputer sehingga Siswa dan Guru memiliki wawasan mengenai komputer dan juga mendapat pengalaman dalam menggunakan, memanfaatkan komputer dan sebagai persiapan untuk ANBK (Asesmen Nasional Berbasis Komputer) atau ANBK sebagai pengganti Ujian Nasional Berbasis Komputer atau UNBK Kata Kunci: Pembelajaran; Pendampingan; Komputerisasi; Microsoft Office; Power Point.